Low-frequency variations with zonal wavenumber 0 in the Southern Hemisphere troposphere (abstract) - Shiotani, Masato (National Institute of Polar Research, 1989)
P(論文) An observational study is made of the low-frequency variations in the southern hemisphere troposphere, using global geopotential height and wind field data for 6 years, from 1980 to 1985,provided by the European Centre for Medium Range Weather Forecasts (ECMWF). Prominent variations with a rhythm of about one to two months are observed in the height field during the southern hemisphere winter and spring. The variations on a hemispheric scale show a barotropic seesaw pattern with an almost circular node around 60 departmental bulletin paper